P398 Long term efficacy and safety of ABP, 501 adalimumab biosimilar in inflammatory bowel diseases: preliminary results from the ADASWITCH study. (21st January 2022) - Cingolani, A; Felice, C; Lombardi, G; Onidi, F M; Checchin, D; Colucci, R; Grossi, L; Ferronato, A; Rocchi, C; Ascolani, M; Binaghi, L; Dore, M F; et al.
Abstract: Background: Adalimumab (ADA) biosimilars have been developed to have a much lower financial cost than ADA originator. The aim of this study was to evaluate the long term efficacy and safety of Adalimumab biosimilar ABP501 in naïve or switched Inflammatory Bowel Diseases (IBD) outpatients in Italian non-tertiary IBD centres Methods: The ADASWITCH study is a multicentric retrospective observational study. Patients treated with Adalimumab ABP501 and with complete clinical, laboratory and endoscopic data, and a minumum follow-up of, 6 months were included. The primary objective was to evaluate the efficacy (defined as persistence on therapy with Adalimumab ABP501) and the safety (rate of adverse events) occurring during treatment. Results: A total of, 117 IBD patients were included:, 83 with Crohn's disease (CD, 38 F, 45 M, 71% naïve) and, 34 with Ulcerative colitis (UC, 16F, 18 M, 61.8% naïve naïve) were included. ABP, 501 showed more efficacy in maintaining clinical response at, 2 years in CD (64 pts, 77, 1%) rather than in UC (22 pts, 64, 7%, p=0.001) and in antiTNF (tumor necrosis factor) naïve (63 pts, 78%) rather than in antiTNF experienced patients (27 pts, 72%, p=0.0014), while no difference was seen in efficacy between ADA-switched and ADA-naïve patients. Nine patients (8 CD, 1 UC, overall, 7, 7%) had adverse events that led to drug discontinuation. Colonic localisation seems to be a predictor of not sustained clinical response (p=0, 002). Conclusion: APB, 501 adalimumab biosimilar showed high rates of efficacy and a good safety profile, in both naïve and shifted IBD patients.